Hubungan Deret Bertingkat Berdasarkan Bilangan Eulerian dengan Operator Beda - Alexander Agung Santoso Gunawan (Bina Nusantara University, 2011)
Rank series defined as: is a generalization of the fixed rank series (the sum of powers), in which its closed solution has been found empirically by Jacob Bernoulli in 1731. This paper will explore the relationship between rank series and differential operator. To see this relationship, examples for the case m = 1.2 and α = 1.2. are provided.